2022
DOI: 10.31234/osf.io/etvn4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decisions From Valuations of Unknown Payoff Distributions

Abstract: Four experiments are presented that clarify the impact of experience on the way people use valuations. In each of the 100 trials of Study 1, participants were asked to choose between the status quo and an unknown binary lottery based on valuations by two expert systems: a well-calibrated “expert” reporting the expected values, and an expert that ignores the low probability outcome and reports the medians (that equaled the modes). The results suggest that experience decreased the inclination to follow the recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Bolton and Katok (2018) study the efficacy of probability forecasts versus recommendation forecasts. They found that forecasts in the form of a recommendation are prone to a "cry wolf effect"-a tendency to ignore the forecast when the forecast has been wrong in the past (also found in previous studies; e.g., Bliss et al, 1995;Erev et al, 2020;Meyer & Bitan, 2002). Overall, probability forecasts performed better.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Bolton and Katok (2018) study the efficacy of probability forecasts versus recommendation forecasts. They found that forecasts in the form of a recommendation are prone to a "cry wolf effect"-a tendency to ignore the forecast when the forecast has been wrong in the past (also found in previous studies; e.g., Bliss et al, 1995;Erev et al, 2020;Meyer & Bitan, 2002). Overall, probability forecasts performed better.…”
Section: Introductionmentioning
confidence: 53%
“…One obvious alternative, natural language descriptions of uncertainty, has been shown to be ambiguous: Interpretation of verbal descriptions of uncertainty are sensitive to context (e.g., Harris & Corner, 2011;Weber & Hilton, 1990) and vary widely by individual (e.g., Karelitz & Budescu, 2004;Wallsten et al, 1986), limiting their ability to deliver a clear message about risk. Recommendations based on expert assessments of the forecast offer a way around both user numeracy and verbal description shortcomings (Erev et al, 2020). Non-numeric in nature, recommendations can, in theory, convey the optimal action to the decision maker as effectively as quantitative measures.…”
Section: Introductionmentioning
confidence: 99%